Climate Change-Induced Agricultural Drought over Moist-Cool and Moist-Warm Climatic Zones: A Case Study in Ale and Adami-Tulu Woredas, in Oromia National Regional State, Ethiopia - Fedhasa Benti; Achalu Chimdi (Universitas Sebelas Maret, 2019)
Frequency and intensity of drought have troubled sustainable agriculture and worsened food insecurity of Ethiopians. This study aimed to investigate climate change-induced agricultural drought over the moist-cool and moist-warm climatic zones, using historical precipitation and temperature data recorded in the crop growing months for 35 years. The changes of temperatures and precipitation were analyzed using Mann Kendall trend test. Agricultural drought indices were analyzed using R-model by withdrawing potential evapotranspiration from precipitation to determine the existing water balance. The values of drought indices were used to characterize the duration, severity, intensity and trends of agricultural drought. Results showed that the changes in maximum and minimum temperatures and precipitation were significantly stronger in the Ale Woreda (P<0.05). However, minimum temperature and precipitation in Adami-Tulu did not noticeably change. The spatial drought events occurred more widely in Ale than in Adami Tulu. The events occurred 12 and 17 times with cumulative severity indices of 41.95 and 48.22 in Ale and Adami-Tulu, respectively. Agricultural drought intensities of the two districts were labeled as “severe” and “moderate dry”, for Ale and Adami-Tulu, respectively. The intensity of drought in Ale district significantly increased (P<0.05) and that in Adami-Tulu negligibly changed. Therefore, the study explicitly showed that more changes in temperature and precipitation aggravated agricultural drought in Ale than in Adami-Tulu more intensely and it is suggested that more attention shall be paid to Ale Woreda.